AB0569 How Often Does Cutaneous Lupus Evolve Into Systemic Lupus? a Uk Cohort Study. (9th June 2015) - Rees, F.; Doherty, M.; Grainge, M.; Lanyon, P.; Davenport, G.; Zhang, W.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic connective tissue disease with a varied clinical phenotype. It can be difficult to define and currently there are no diagnostic criteria. Classification criteria have been developed to standardise entry to research studies and often these are used as a surrogate. However, in clinical practice there are people diagnosed with "lupus" who do not meet the classification criteria, for example those with single organ disease or only meeting 3 criteria. Cutaneous manifestations of lupus are common and may appear in isolation. It is not yet possible to predict from clinical presentation who will remain cutaneous only lupus and who will develop systemic disease and whether we can target therapy to prevent progression from single-organ to systemic disease. Objectives: We aimed to ascertain from a community perspective 1) the first diagnosis given to people with lupus, 2) what proportion of lupus patients are diagnosed with cutaneous lupus, and 3) what proportion of these people will go on to develop systemic disease. Methods: A retrospective cohort study was conducted using the UK Clinical Practice Research Datalink, a longitudinal database of anonymised general practice records deemed to be broadly representative of the UK population. Data are entered at the practice using Read codes, a standard clinical terminology system used in the UK. Incident cases of lupus were identified during the period 1999-2012 as those with any one of 24 Read codes for lupus or a lupus subtype. The first code was taken as the date of diagnosis. For those with a cutaneous only diagnosis subsequent systemic codes were noted. Results: 3479 cases of "lupus" were diagnosed between 1999 and 2012 (incidence 6.23/100, 000 person-years (95% CI: 6.03-6.44)). The three most common initial diagnoses were SLE (48%), lupus erythematosus (LE) (18%) and discoid lupus (DLE) (21%). 1002 (29%) had only cutaneous lupus at diagnosis and of these 145 (14%) developed a subsequent systemic diagnosis in the medical record (Figure 1 ). The cutaneous codes at diagnosis in these 145 were DLE 70%, subacute cutaneous LE 26%, lupus erythematosus tumidus 1%, lupus erythematosus profundus 1% and lupus erythematosus chronicus 1%. The subsequent systemic diagnoses for these 145 people were LE in 52%, SLE 41%, disseminated LE 4%, lung disease with SLE 1%, SLE not otherwise specified 1% and polyneuropathy in disseminated LE 1%. Conclusions: Although the most common form of lupus in the community is SLE, a quarter of people with lupus have cutaneous only lupus. 14% of patients presenting with cutaneous lupus will develop systemic disease. Further research could examine predictors at diagnosis for disease progression and examine whether targeted therapy in this cohort could prevent disease progression. Disclosure of Interest: F. Rees: None declared, M. Doherty Consultant for: Ad hoc advisory boards on osteoarthritis and gout: Astrazeneca, Menarini, Nordic Biosciences, Novartis, Pfizer, M. Grainge: None declared, P. Lanyon Consultant for: Advisory board for Eli Lilly, Speakers bureau: Pfizer, G. Davenport Speakers bureau: MSD, Pfizer, Lilly, Menarini, Servier, Prostrakan, Amgen, GSK, and Consilient, W. Zhang Consultant for: Savient for Pegloticase, Speakers bureau: Daiichi Sankyo for topical loxoprofen patches